ANALYZING THE FACTOR-POINT SCALE OF PAY FOR CIVIL SERVANTS: EXPLORING BENEFITS, DRAWBACKS, AND EVALUATING ITS IMPACT ON HUMAN RESOURCES - Janzakova, Urkiya; Omarov, Daniyal; Kairolda, Azamat (Nazarbayev University Graduate School of Public Policy, 2024)
This study is a comprehensive analysis of the Factor-Point Scale of Pay model applied in Kazakhstan’s civil service. It researches the impact of the FPS compensation system on different dimensions of the civil service such as recruitment, retention, and overall performance of civil servants. With the use of a mixed-methods approach, the study analyses the work and influence of the Astana Civil Service Hub (ACSH) as a primary venue for research. By assessing how effectively the Factor-Point Scale of Pay aligns with the country’s strategical objectives for the civil service excellence. Throughout the research, the study uncovered both the strengths and weaknesses of the compensation model. It highlighted the system’s positive aspects, such as its objective and transparent nature, which contribute to fairness and trust within the civil service. However, the research also shed light on potential drawbacks, such as the system’s rigidity in rewarding exceptional performance and its possible impact on talent acquisition and retention. The core findings emphasized the need for a nuanced understanding of how the Factor-Point Scale operates within the specific context of Kazakhstan. This includes considering the system’s adaptability to market-driven changes and its ability to attract and retain top talent within the civil service. As an outcome of the study a several recommendations were developed in order to support the continious implementation of FPS and its improvement. These recommendations are focused on enhancing flexibility within the compensation model, aligning it more precisely with evolving market trends, and leveraging the expertise of ACSH in enhancing the capacity of the civil service in Kazakhstan and fostering the innovation. Ultimately, the research aimed to contribute to the evolution of a more responsive, efficient, and motivated civil service system in Kazakhstan.
Keywords: Factor-Point Scale of Pay Model; Civil Service Reform; Motivation and Job Satisfaction; Public Sector Compensation; Astana Civil Service Hub; Performance-based Pay; Type of access: Embargo